800MPa-grade high-strength weathering steel with specification of less than or equal to 10mm and production method thereof

The 800MPa grade high-strength weathering steel with a composition of 0.030≤C≤0.050% and a quasi-polygonal ferrite + acicular ferrite structure addresses the issue of poor low-temperature toughness, achieving high mechanical properties and corrosion resistance for applications in structural engineering.

CN119177400APending Publication Date: 2024-12-24PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535092.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing 800MPa grade high-strength weathering steel is primarily thin and suffers from poor low-temperature toughness.

Method used

A chemical composition of 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.12%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.085%≤Ti≤0.100%, 0.020%≤Nb≤0.030%, N≤0.0040%, O≤0.0020% with a quasi-polygonal ferrite + acicular ferrite structure and nano-precipitation phase, produced through smelting, precise heating, rapid cooling, and medium-high temperature coiling.

Benefits of technology

The solution results in high-strength weathering steel with excellent mechanical properties, low-temperature toughness, and atmospheric corrosion resistance, suitable for applications in railway vehicles, containers, towers, and bridge engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177400A_ABST
    Figure CN119177400A_ABST
Patent Text Reader

Abstract

The invention discloses 800 MPa-grade high-strength weathering steel with the specification smaller than or equal to 10 mm and a production method of the 800 MPa-grade high-strength weathering steel, and belongs to the technical field of metallurgy. The steel plate comprises the following components in percentage by mass: 0.030% < = C < = 0.050%, 0.10% < = Si < = 0.20%, 1.20% < = Mn < = 1.30%, 0.050% < = P < = 0.060%, 0.003% < = S, 0.010% < = Als < = 0.050%, 0.90% < = Cr < = 1.00%, 0.12% < = Ni < = 0.20%, 0.30% < = Cu < = 0.35%, 0.085% < = Ti < = 0.100%, 0.020% < = Nb < = 0.030%, 0.0040% < = N, 0.0020% < = O and the balance of Fe and impurities. The V-shaped notch impact energy KV2 of a 3 / 4 size sample at-40 DEG C is greater than or equal to 60J, and the V-shaped notch impact energy KV2 of a 1 / 2 size sample at-40 DEG C is greater than or equal to 40J.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and specifically relates to 800MPa-grade high-strength weathering steel with a specification of ≤10mm and a production method thereof. Background Art

[0002] Weathering steel, also known as atmospheric corrosion resistant steel, is a low alloy steel between ordinary steel and stainless steel. It is widely used in railways, vehicles, bridges, towers, photovoltaics, high-speed engineering and other steel structures that are exposed to the atmosphere for a long time. Under the background of "increasing speed, reducing deadweight, and increasing load" in my country's railway freight transportation, high strengthening and lightweight are the development direction of weathering steel for railway containers. At present, the steel plates mainly used for weathering steel for railway containers are weathering steels with yield strengths of 345MPa and 450MPa. The unit weight is heavy, and the amount of steel used and transportation costs are high. Without reducing the performance of the material, increasing the strength of the steel and reducing the thickness of the steel is an effective way to achieve lightweight components in the corresponding field.

[0003] The Chinese invention patent with publication number CN115161551B discloses a high-strength, high-formability, super-atmospheric corrosion-resistant steel and its manufacturing method, whose mass percentage content is: C: 0.04% to 0.10%, Si≤0.50%, Mn: 0.20% to 1.80%, P≤0.03%, S≤0.01%, Al≤0.30%, Cu: 0.10% to 0.60%, Cr: 1.5% to 4.5%, Ti: 0.04% to 0.18%, N≤0.008%, the balance includes Fe and other unavoidable impurities; and at the same time, it must meet: C≥0.08%-Ti / 3, Mn+Cr≥2.0%. The invention achieves high corrosion resistance and high strength and high formability of the steel plate by adding a high content of Cr and Al, but its N content is generally high, and it is easy to form coarse TiN particles with Ti, which leads to a significant decrease in low-temperature impact toughness, especially the large fluctuation of impact energy under the condition of ≤-40℃.

[0004] The Chinese invention patent with publication number CN113278879B discloses an atmospheric corrosion resistant 800MPa grade thin gauge high-strength weathering steel plate and a production method thereof, wherein the mass percentages thereof are: C: 0.06% to 0.09%, Si: 0.30% to 0.50%, Mn: 0.70% to 1.00%, P: ≤0.015%, S: ≤0.005%, Cr: 0.60% to 1.00%, Ni: 0.05% to 0.10%, Cu: 0.25% to 0.40%, Als: 0.020% to 0.045%, Ti: 0.080% to 0.110%, Nb: 0.015% to 0.030%, N≤0.0040%, O≤0.0035%, and the remainder is Fe and unavoidable impurity elements. The invention relates to steel plates with a thickness of ≤6.0 mm, but not to steel plates with a thickness of >6.0 mm. Moreover, due to the relatively high C content, more cementite is easily produced when producing thicker steel plates, resulting in deterioration of low-temperature toughness.

[0005] The Chinese invention patent with publication number CN107190202B discloses a method for producing steel for railway containers with a tensile strength ≥800MPa by continuous casting and rolling of thin slabs, wherein the steel has the following mass percentages: C: 0.08% to 0.12%, Si: 0.15% to 0.25%, Mn: 1.3% to 1.5%, P: ≤0.010%, S: ≤0.008%, Cu: 0.30% to 0.60%, Cr: 0.50% to 0.80%, Nb: 0.010% to 0.025%, Ti: 0.141% to 0.162%, Als: 0.015% to 0.020%, N: ≤0.005%, and the remainder is Fe and unavoidable impurities. This invention relates to steel plates with a thickness of less than 4.0 mm, and does not involve the performance of thicker steel plates. In addition, due to the relatively high C content, more cementite is easily produced when producing thicker steel plates, resulting in deterioration of low-temperature toughness.

[0006] The Chinese invention patent with publication number CN117947354A discloses a weather-resistant hot-rolled steel strip and its production method, and a weather-resistant steel strip, whose mass percentage is: C: 0.03%~0.09%, Si: 0.05%~0.30%, Mn: 0.4%~1.8%, P: 0.04%~0.07%, S: ≤0.0050%, Cr: 1.0%~4.0%, Cu: 0.20%~0.50%, Al: 0.01%~0.05%, Ti: 0.09%~0.15%, N: ≤0.0060%, and the rest is Fe and unavoidable impurities. The invention relates to steel plates with a thickness of ≤6.0mm, but not to steel plates with a thickness of >6.0mm. Moreover, since the N and Ti contents are generally high, coarse TiN particles are easily formed, which leads to a significant reduction in low-temperature impact toughness, especially the large fluctuation of impact energy under conditions of ≤-40℃.

[0007] In summary, the prior art does not involve the preparation of high-strength, high-low temperature toughness and high weather resistance structural steel with a thickness of ≤10 mm. Summary of the invention

[0008] The technical problem to be solved by the present invention is that the existing 800MPa grade high-strength weathering steel is mainly thin in size and has poor low-temperature toughness.

[0009] The technical solution adopted by the present invention to solve the technical problem is as follows: the present invention provides a 800MPa grade high-strength weathering steel with a specification of ≤10mm, wherein the chemical composition of the steel is as follows by mass percentage: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.12%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.085%≤Ti≤0.100%, 0.020%≤Nb≤0.030%, N≤0.0040%, O≤0.0020%, and the balance is Fe and unavoidable impurities.

[0010] The thickness of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm is 3.0mm to 10.0mm.

[0011] The microstructure of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm is quasi-polygonal ferrite + acicular ferrite structure + nano-precipitation phase.

[0012] The mechanical properties of the above 800MPa grade high strength weathering steel with a specification of ≤10mm are R eL ≥690MPa, R m ≥800MPa, A≥15%.

[0013] The bending performance of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm is that there is no crack in the 180° bending test D=2a at room temperature.

[0014] The low-temperature impact toughness of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm under -40℃ is: V-notch impact energy of 3 / 4 size specimen KV 2 ≥60J, 1 / 2 size specimen V-notch impact energy KV 2 ≥40J.

[0015] The present invention also provides a method for producing the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm, comprising the following steps:

[0016] a. Smelting: Smelt the ingot according to the chemical composition of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm;

[0017] b. Heating: The heating temperature of the casting is 1250±10℃, the heating time is 200~280min, and the holding time is ≥35min;

[0018] c. Rough rolling: The thickness of the intermediate billet at the rough rolling outlet is 40mm to 55mm;

[0019] d. Finishing rolling: When the finished product thickness is less than 6.0mm, the finishing rolling entrance temperature is 1030-1080℃, and the final rolling temperature is 840-870℃; when the finished product thickness is 6.0mm-10.0mm, the finishing rolling entrance temperature is 980-1020℃, and the final rolling temperature is 830-860℃;

[0020] e. Laminar cooling: adopt the front-stage rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 610℃~640℃;

[0021] f. Coiling: Coiling temperature 590℃~620℃.

[0022] In step a of the above production method, the smelting includes: molten iron desulfurization → converter → RH vacuum treatment → LF refining → slab continuous casting.

[0023] Furthermore, in the above smelting process, high carbon ferromanganese is used for manganese matching in the converter without decarburization.

[0024] Furthermore, in the above smelting process, decarburization is performed during the RH vacuum treatment.

[0025] Furthermore, in the above smelting process, quantitative and precise carbon addition is carried out during LF refining.

[0026] In step c of the above production method, when the thickness of the intermediate billet is ≤45 mm, the intermediate billet is coiled and descaled by a hot coil box.

[0027] In step f of the above production method, after coiling is completed, the steel sheet is slowly cooled to room temperature in a slow cooling pit.

[0028] The beneficial effects of the present invention are as follows: the present invention adopts slightly low C, Ti-Nb composite micro-alloying, low-cost alloy design and easy-to-implement production process flows such as precise heating, rapid cooling in the front section, and medium and high temperature coiling to obtain 800MPa grade high-strength weathering steel with good surface quality, excellent mechanical properties, low-temperature toughness and atmospheric corrosion resistance. The obtained steel plates and steel strips are widely used in railway vehicles, containers, towers, highways and bridge engineering and other fields, and have broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The microstructure of the finished steel obtained in Example 2-2. DETAILED DESCRIPTION

[0030] The technical solution of the present invention can be specifically implemented in the following manner.

[0031] The invention discloses an 800MPa grade high-strength weathering steel with a specification of ≤10mm, whose chemical composition is as follows by mass percentage: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.12%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.085%≤Ti≤0.100%, 0.020%≤Nb≤0.030%, N≤0.0040%, O≤0.0020%, and the balance is Fe and unavoidable impurities.

[0032] The alloy composition design principle of the present invention is as follows:

[0033] C: must have a certain content to promote the formation of carbide strengthening phase, thereby ensuring the strength level of the steel strip. When its content is too high, the precipitated carbide particles will increase, which is not conducive to the hole expansion performance of the steel plate; when its content is too low, the strength cannot meet the design requirements. The present invention sets the C content to 0.030% to 0.050%, and forms nano-TiC and (Ti, Nb) C precipitation phases by adding Ti and Nb, fixes free C, and reduces Fe 3 C content, while achieving the purpose of strengthening ferrite.

[0034] Si: It has a solid solution strengthening effect, which can simultaneously improve the strength and elongation of the steel strip and improve the formability of the steel strip. Usually, the silicon content should not be less than 0.30%. However, when the Si content is high, Fe 2 SiO 4 Red rust is not easy to remove during pickling. In order to improve the surface quality of the steel strip and reduce the difficulty of smelting in the steel plant itself and the difficulty of removing red rust iron scale for users, the Si content is designed to be 0.10% to 0.20% in the present invention.

[0035] Mn: It is a solid solution strengthening element. According to the strength requirements of this steel grade, when the content is too low, the strength will not meet the design requirements; when the content is too high, the proportion of pearlite will increase, and high Mn content will easily lead to Mn component segregation in the ingot, which is one of the main reasons for the appearance of banded structure in the steel strip, and the banded structure will cause the plastic toughness of the steel strip to drop sharply. At the same time, for carbon manganese steel, the interaction between C and Mn has a certain influence on the formation and distribution of pearlite structure. When the content of both is too high, coarse pearlite and banded structure are easily generated. Therefore, under the premise that the strength meets the design requirements, the C content and Mn content are designed to be as low as possible. In the present invention, the Mn content is 1.20% to 1.30%.

[0036] P: As the strongest element for strengthening ferrite, it has strong solid solution strengthening and cold work hardening effects. When used as an alloying element, it can improve its strength and atmospheric corrosion resistance of the steel strip. However, when the content is too high, the cold stamping performance of the steel strip will drop sharply. At the same time, there will be segregation of the components of the continuous casting slab, causing uneven structure, increasing temper brittleness, and significantly reducing the plasticity and toughness of the steel strip, so that the steel strip will appear "cold brittle" phenomenon and brittle cracking during cold working. However, with the advancement of metallurgical technology, the segregation of P-containing steel leads to a significant reduction in the plasticity and toughness risks of the steel strip, creating conditions for the development of high-strength and high-weathering steel with high content. The P content of the present invention is 0.050% to 0.060%.

[0037] S: It is an impurity element in steel and is easy to form MnS in steel. The amount and shape of sulfides in steel directly affect the hole expansion performance of steel strip, especially strip sulfide inclusions are prone to cracks during deformation, so the designed S content is ≤0.003%.

[0038] Al: Its basic function in the present invention is deoxidation in the steelmaking process. The Als content in steel is generally less than 0.010%; at the same time, if the Als content exceeds 0.060%, its grain refinement effect is weakened. The present invention sets the Als content to 0.010% to 0.050%.

[0039] Cr: It can delay the pearlite transformation, significantly improve the hardenability of steel, facilitate the formation of bainite structure, and refine the structure to achieve a strengthening effect. Too high Cr content will deteriorate the processing and formability of the material. The principle of selecting the Cr content is to promote the formation of bainite and avoid the formation of martensite structure which has an adverse effect on elongation. Therefore, the Cr content in the present invention is 0.90% to 1.00%.

[0040] Ni: Ni can significantly improve the corrosion resistance of steel. At the same time, nickel and copper elements form a Ni-containing copper-rich phase, which is retained in the outer oxide layer in a solid state, reducing the copper enrichment in the matrix and the chance of forming a liquid copper-rich phase, thereby avoiding the occurrence of hot brittle defects. Therefore, Ni / Cu in steel is generally controlled to be ≥1 / 2; but too high nickel will increase the adhesion of the oxide scale, and pressing it into the steel will form hot rolling defects on the surface. Nickel is a precious metal, and too high a content thereof will significantly increase the alloy cost of the steel; therefore, the Ni content in the present invention is 0.12-0.20%.

[0041] Cu: Cu is conducive to forming a dense, well-adhesive amorphous oxide (hydrocarbon oxide) protective layer on the surface of steel, and has a significant corrosion resistance effect; copper and sulfur generate insoluble sulfides, thereby offsetting the harmful effects of S on the corrosion resistance of steel; according to the calculation formula of atmospheric corrosion resistance index I, too little or too much copper content will reduce the calculated value of I, and the peak value of Cu content is 0.35%. Therefore, the Cu content in the present invention is 0.30-0.35%.

[0042] Ti, N: Titanium combined with carbon and nitrogen can form tiny carbonitrides to pin grain boundaries, delay recrystallization, inhibit the growth of austenite grains, and produce fine grain strengthening and precipitation strengthening effects; increasing the titanium content can increase the volume fraction of its carbonitrides, enhance the fine grain strengthening and precipitation strengthening effects; increasing the nitrogen content in the steel is conducive to promoting the precipitation of the second phase of titanium; but too high a titanium or nitrogen content is likely to form large-sized TiN, resulting in reduced bending performance, impact performance, and forming performance, and too high a nitrogen content will increase the aging tendency and cold brittleness and hot brittleness of the steel, and damage the welding performance and cold bending performance of the steel; therefore, the Ti content in the present invention is 0.085-0.100%, and the N content is ≤0.0040%.

[0043] Nb: Nb can pin austenite grain boundaries to prevent grain growth, ultimately refining the grains, which is beneficial to improving strength, plasticity, and toughness; but Nb is a precious metal, and excessive content thereof will significantly increase production costs; therefore, the Nb content in the present invention is 0.020-0.030%.

[0044] O: As a harmful element in steel, it is also an unavoidable element in the steelmaking process. The present invention realizes ultra-low oxygen content control through RH vacuum treatment, and the O content is ≤0.0020%.

[0045] Production method of the above-mentioned 800MPa grade high-strength weathering steel with a specification of ≤10mm:

[0046] (1) Smelting process: The smelting process includes the following processes: “hot iron desulfurization → converter → RH vacuum treatment → LF refining → slab continuous casting”. In the converter process, high carbon ferromanganese is used for manganese matching without decarburization. RH vacuum treatment is then performed for decarburization. Then, quantitative and precise carbon addition is performed in LF. This technology can use relatively cheap high carbon ferromanganese alloy, reduce the consumption of aluminum deoxidizer, and significantly reduce iron loss and oxygen content in molten steel.

[0047] (2) Heating process: To ensure that alloy elements such as Ti, Mn, Cr, and B are fully dissolved, the heating temperature of the continuous casting slab is 1250±10℃, and the heating time is 200-280min, of which the holding time is ≥35min.

[0048] (3) Rough rolling process: The thickness of the intermediate billet at the rough rolling outlet is 40 mm to 55 mm.

[0049] (4) Hot coil box: When the thickness of the intermediate billet is ≤45mm, the intermediate billet is coiled and scaled.

[0050] (5) Finishing process:

[0051] ① When the finished product thickness is less than 6.0mm, the finishing rolling entrance temperature is 1030-1080℃, and the final rolling temperature is 840-870℃;

[0052] ② When the finished product thickness is 6.0mm-10.0mm, the finishing rolling entrance temperature is 980-1020℃, and the final rolling temperature is 830-860℃;

[0053] (6) Laminar cooling process: After finishing rolling, the steel strip adopts the front-end rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 610℃~640℃.

[0054] (7) Coiling temperature: To ensure that there are enough nano-sized TiC and (Ti, Nb) C, and under the action of the strong hardenability element Cr, the coiling temperature is 590-620°C, and then it is coiled and slowly cooled to room temperature in a cooling pit.

[0055] The technical solution and effects of the present invention are further illustrated below through practical examples.

[0056] Example

[0057] In order to further understand the present invention, the present invention provides three groups of embodiments 1 to 3 for preparing 800MPa grade high-strength weathering steel with a specification of ≤10mm using the chemical composition and production method of the present invention. The chemical composition is shown in Table 1, and the remainder is Fe and unavoidable impurities.

[0058] Table 1 Chemical composition (by mass percentage, %)

[0059] project Example 1 Example 2 Example 3 C 0.032 0.041 0.049 Si 0.19 0.11 0.15 Mn 1.30 1.22 1.25 P 0.055 0.060 0.052 S 0.0013 0.0029 0.0021 Als 0.020 0.046 0.024 Cr 0.92 0.96 1.00 Ni 0.16 0.19 0.20 Cu 0.31 0.35 0.33 Ti 0.087 0.093 0.099 Nb 0.026 0.022 0.030 N 0.0025 0.0034 0.0029 O 0.0014 0.0011 0.0018

[0060] The ingot was smelted according to the composition shown in Table 1, and high-strength weathering steel was prepared by heating, rough rolling, finishing rolling, laminar cooling, coiling and other processes, wherein the key process parameters are shown in Table 2. At the same time, the chemical composition in Example 3 in Table 1 was used to prepare a comparative steel by heating, rough rolling, finishing rolling, laminar cooling, coiling and other processes, wherein the process parameters are shown in Table 2.

[0061] Table 2 Process parameters

[0062]

[0063] The mechanical properties, bending properties, low-temperature toughness and microstructure type of the high-strength weathering steel prepared above were tested, and the results are shown in Table 3.

[0064] Figure 1 The microstructure of the finished steel obtained in Example 2-2. As can be seen from the figure, the microstructure of the 800MPa grade high-strength weathering steel with a specification of ≤10mm described in the present invention is quasi-polygonal ferrite (QF) + acicular ferrite structure (AF) + nano-precipitation phase (MC).

[0065] Table 3 Test results

[0066]

Claims

1. A 800MPa grade high-strength weathering steel with a specification of ≤10mm, characterized in that: Its chemical composition by mass percentage is: 0.030≤C≤0.050%, 0.10%≤Si≤0.20%, 1.20%≤Mn≤1.30%, 0.050%≤P≤0.060%, S≤0.003%, 0.010%≤Als≤0.050%, 0.90%≤Cr≤1.00%, 0.12%≤Ni≤0.20%, 0.30%≤Cu≤0.35%, 0.085%≤Ti≤0.100%, 0.020%≤Nb≤0.030%, N≤0.0040%, O≤0.0020%, and the balance is Fe and unavoidable impurities.

2. The 800MPa grade high-strength weathering steel with a specification of ≤10mm according to claim 1, characterized in that: The thickness of the weathering steel is 3.0 mm to 10.0 mm.

3. The 800MPa grade high-strength weathering steel with a thickness of ≤10mm according to claim 1, characterized in that: The microstructure of the weathering steel is quasi-polygonal ferrite+acicular ferrite structure+nano precipitate phase.

4. The 800MPa grade high-strength weathering steel with a thickness of ≤10mm according to claim 1, characterized in that: The mechanical properties of the weathering steel are R eL ≥690MPa, R m ≥800MPa, A≥15%.

5. The 800MPa grade high-strength weathering steel with a thickness of ≤10mm according to claim 1, characterized in that: The bending performance of the weathering steel is that there is no crack in the 180° bending test D=2a at room temperature.

6. The 800MPa grade high-strength weathering steel with a thickness of ≤10mm according to claim 1, characterized in that: The low-temperature impact toughness of the weathering steel at -40°C is: the V-notch impact energy KV2 ≥ 60J for a 3 / 4 size specimen, and the V-notch impact energy KV2 ≥ 40J for a 1 / 2 size specimen.

7. A method for producing 800MPa grade high-strength weathering steel with a specification of ≤10mm, characterized in that: The steps include: a. Smelting: Smelting the ingot according to the chemical composition of claim 1; b. Heating: The heating temperature of the casting is 1250±10℃, the heating time is 200~280min, and the holding time is ≥35min; c. Rough rolling: The thickness of the intermediate billet at the rough rolling outlet is 40mm to 55mm; d. Finishing rolling: When the finished product thickness is less than 6.0mm, the finishing rolling inlet temperature is 1030-1080℃, and the final rolling temperature is 840-870℃; when the finished product thickness is 6.0mm-10.0mm, the finishing rolling inlet temperature is 980-1020℃, and the final rolling temperature is 830-860℃; e. Laminar cooling: adopt the front-stage rapid cooling method, the laminar cooling rate is ≥70℃ / s, and the midpoint temperature is 610℃~640℃; f. Coiling: Coiling temperature 590℃~620℃.

8. The method for producing a 800MPa grade high-strength weathering steel with a specification of ≤10mm according to claim 7, characterized in that: In step a, the smelting includes molten iron desulfurization → converter → RH vacuum treatment → LF refining → slab continuous casting, specifically: high carbon ferromanganese is used for manganese matching without decarburization in the converter, decarburization is performed during RH vacuum treatment, and quantitative and precise carbon addition is performed during LF refining.

9. The method for producing a 800MPa grade high-strength weathering steel with a specification of ≤10mm according to claim 7, characterized in that: In step c, when the thickness of the intermediate billet is ≤45 mm, the intermediate billet is coiled and scaled by a hot coil box.

10. The method for producing a 800MPa grade high-strength weathering steel with a specification of ≤10mm according to claim 7, characterized in that: In step f, after coiling is completed, the steel sheet is slowly cooled to room temperature in a slow cooling pit.